Faktor-Faktor Yang Mempengaruhi Kinerja Perusahaan Dimoderasi Oleh Financial Technology - Irmawati H. R.; Jamaluddin Majid; Suhartono Suhartono (LPPM ISNJ Bengkalis, 2022)
This study analyzes the effect of financial inclusion, financial literacy, and financial behavior on company performance using financial technology as a moderating variable. This study uses quantitative methods. The population in this study is medium-sized businesses in Makassar City. Sampling using purposive sampling in order to obtain a sample of 53. The data of this study is primary data extracted from respondents who have implemented financial technology through questionnaires. Data were analyzed using multiple linear regression techniques and moderate regression analysis (MRA). The study's multiple linear regression results indicate that financial literacy has a significant positive effect on company performance. Financial inclusion and financial behavior do not affect company performance. The MRA results show that financial technology does not moderate the effect of financial inclusion, financial literacy, and financial behavior on company performance. However, the use of financial technology is more appropriate as a predictor. This research contributes as input for relevant agencies to pay special attention to the development of company performance and becomes a facilitator for medium-sized businesses in improving their understanding of financial aspects.